The Influence Of NPF, Bopo, Current Ratio and Gearing Ratio On Financing Company Performance (Comparation Study Of Financing Companies In Indonesia Before and During The Covid-19 Period) - Rizky Muhammad Harris; Wisnu Mawardi (Politeknik Siber Cerdika Internasional, 2023)
This research aims to compare the effect of Non Performing Financing (NPF), Operating Expense to Operating Income (BOPO), Current Ratio, and Gearing Ratio of financing companies in Indonesia on profitability performance as represented by the variable Return on Assets (ROA) in pre-COVID-19 and during COVID-19 times. This type of research is quantitative research using time series data with the period before the spread of COVID-19 was for the period September 2018 to February 2020 and the period during the spread of COVID-19 was March 2020 to August 2021. The data source used is based on monthly reports submitted by financing company in Indonesia to the Financial Services Authority. The analysis used in this research is multiple linear regression and the Chow test. The classical assumption test on the data used has been carried out including the normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test before carrying out the multiple linear regression test. The research results obtained were that before the COVID-19 pandemic NPF had no effect on ROA, BOPO had a negative and significant effect on ROA, Current Ratio had no effect on ROA, and Gearing Ratio had no effect on ROA. While during the COVID-19 pandemic it was known that NPF had no effect on ROA, BOPO had no effect on ROA, Current Ratio had no effect on ROA, and Gearing Ratio had a positive and significant effect on ROA. The results of the Chow test showed that there were differences in the effect of NPF, BOPO, Current Ratio, and Gearing Ratio on the ROA of financing companies in Indonesia before COVID-19 and during the COVID-19 period.